Blockchain and IoT Integration for Secure Healthcare Data Management: A Narrative Review - Setiawan, Adi Wahyu (Digitus : Journal of Computer Science Applications, 2025)
The convergence of blockchain and Internet of Things (IoT) technologies has the potential to revolutionize secure data management in healthcare systems. This narrative review investigates how this integration addresses critical issues such as data privacy, interoperability, energy efficiency, and systemic barriers in healthcare. Literature was gathered from databases including Scopus, Web of Science, and Google Scholar, using keyword combinations such as "Blockchain AND IoT AND Healthcare" and "Cybersecurity AND IoT AND Data Privacy". Studies published between 2018 and 2024 were included based on clear methodological standards and relevance to healthcare applications. The review reveals that blockchain significantly enhances the security, transparency, and accessibility of personal health data while enabling efficient remote monitoring through IoT integration. It also highlights that smart contracts and AI-augmented systems optimize operations, reduce delays, and lower costs. However, challenges such as poor infrastructure, low digital literacy, and fragmented regulations impede widespread adoption. Notably, the impact of these factors varies across developed and developing countries. These findings suggest that policy reforms, increased investment in infrastructure, and public education are vital to advancing technological uptake. The study concludes that blockchain-IoT systems represent a strategic innovation in healthcare but require holistic, cross-sector collaboration to realize their transformative potential.